2010
DOI: 10.1007/s11205-010-9586-7
|View full text |Cite
|
Sign up to set email alerts
|

Good Job, Good Life? Working Conditions and Quality of Life in Europe

Abstract: Job quality, Life satisfaction, Quality of life, Europe, Cross-national comparison,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 50 publications
2
122
1
10
Order By: Relevance
“…Jo-Hui Lin, Jehn-Yih Wong and Ching-hua Ho (2013) found that work-leisure conflict is inversely correlated to quality of life, whereas the leisure benefit system contentment is clearly associated with the quality of life. Sonja Drobnic, Barbara Beham and Patrick Prag (2010) life satisfaction improves the quality of life among the respondents working in the nine European countries. Hossein Mobaraki et al, (2017) identified that quality of work life has a strongly related with the occupational satisfaction among the 251 Audiologists in Iran.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Jo-Hui Lin, Jehn-Yih Wong and Ching-hua Ho (2013) found that work-leisure conflict is inversely correlated to quality of life, whereas the leisure benefit system contentment is clearly associated with the quality of life. Sonja Drobnic, Barbara Beham and Patrick Prag (2010) life satisfaction improves the quality of life among the respondents working in the nine European countries. Hossein Mobaraki et al, (2017) identified that quality of work life has a strongly related with the occupational satisfaction among the 251 Audiologists in Iran.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Összességében tehát a szakirodalom azt mutatja, hogy a munkával való elégedettség releváns, érvényes és megbízható mutató, amely összefüggésben áll a munkahelyi teljesítménnyel, azaz alaposabb elemzése nem érdektelen. (Booth-van Ours 2008, 2009, Clark 1996, 2010Cornelißen 2009, Drobnič-Beham-Präg 2010, Helliwell-Huang 2010, PichlerWallace 2009, Skalli-Theodossiou-Vasileiou 2008, Sousa-Poza-Sousa-Poza 2000, van der MeerWielers 2013. Ilyen elemzések elsősorban az utóbbi két évtizedben készültek, többek között a nemzetközi összehasonlításra egyre inkább alkalmas adatfelvételek elterjedésének köszönhetően.…”
Section: A Munkával Való Elégedettségunclassified
“…Jellemzően vagy egy-egy országra korlátozódnak az elemzések (Clark 1996, Cornelißen 2009, Helliwell-Huang 2010, vagy a munkával való elégedettséget mérő változó hiányában az élettel való elégedettséget vagy a boldogságot használják függő változóként (Drobnič et al 2010, HelliwellHuang 2010, van der Meer-Wielers 2013. Továbbá gyakori, hogy a szerzők egy-egy kitüntetett szempontra (például a munkaidő hatásának elemzésére) koncentrálnak (Booth-van Ours 2008, 2009Knabe-Rätzel 2010, Pouwels-Siegers-Vlasblom 2008 , a kérdezett partnerrel él-e, a háztartás nagysága, a lakóhely településtípusa (3 kategóriában).…”
Section: áBra a Termelékenység éS A Munkával Való Elégedettség Kapcsunclassified
“…In the first place, the Scandinavians formulated the background of QWL in the 1950s, with the theory of sociotechnical movements, which involves two dimensions: the social one and the technological one (3,4). The main characteristic is conceiving workers as generators of products or services through technology, but at the same time, considering the latter as a factor that brings changes in people and, therefore, how they are able to pursue their wellbeing through controlling and directing the determinants of their resources (economic and social) toward the improvement of their living conditions (2,3). One of its characteristics is the fact that it is based on the theory of systems and it aims to increase work performance by applying job reorganization as an organizational strategy, where workers use their skills to do their job and develop personal skills (3,4).…”
Section: Introductionmentioning
confidence: 99%